Influence of the Vitreomacular Interface on Treatment Outcomes in the Comparison of Age-Related Macular Degeneration Treatments Trials - Ciulla, Thomas A; Cuilla, Thomas A; Ying, Gui-Shuang; Maguire, Maureen G; Martin, Daniel F; Jaffe, Glenn J; Grunwald, Juan E; Daniel, Ebenezer; Toth, Cynthia A (Ophthalmology (Rochester, Minn.), 2015)
To assess the association of the vitreomacular interface with outcomes of eyes treated with anti-vascular endothelial growth factor drugs for neovascular age-related macular degeneration (AMD). Prospective cohort study within a multicenter, randomized clinical trial. Patients enrolled in the Comparison of AMD Treatments Trials (CATT). Treatment was assigned randomly as either ranibizumab or bevacizumab and as 3 different regimens for dosing over a 2-year period. Masked readers at a reading center assessed optical coherence tomography (OCT) scans at baseline and follow-up for vitreomacular traction (VMT) and vitreomacular adhesion (VMA), fluid, and central thickness. Visual acuity (VA) was measured by masked, certified examiners. Anatomic features and VA at baseline and 1 and 2 years and number of treatments. At baseline, 143 patient eyes (12.8%) had VMT or VMA. Compared with those with neither (n = 972), patients with VMT or VMA were younger (mean ± standard error, 75.5 ± 0.6 vs. 79.7 ± 0.24 years; P < 0.0001) and more likely to be male (52.4% vs. 36.2%; P = 0.0003), to be cigarette smokers (68.5% vs. 55.3%; P = 0.003), and to have subretinal fluid on OCT (86.7% vs. 81.0%; P = 0.047). Vitreomacular interface status was not associated with VA at baseline or follow-up. Among eyes treated as needed (n = 598) and followed up for 2 years (n = 516), the mean number of injections was 15.4 ± 0.9 for eyes having VMT at baseline or during follow-up (n = 60), 13.8 ± 0.7 for eyes with VMA at baseline or follow-up (n = 79), and 12.9 ± 0.4 (P = 0.02) for eyes without VMT or VMA (n = 377). In addition, the mean number of injections in eyes treated as needed increased from 13.0 ± 0.3 when VMT was not observed to 13.6 ± 1.3 when observed once and to 17 ± 1.2 when observed more than once during follow-up. At 2 years, geographic atrophy developed in a lower percentage of eyes with VMT or VMA at baseline (11.7%) than with neither condition (22.5%; P = 0.005). In eyes in the CATT, VMT and VMA were infrequent. At baseline and follow-up, VMT or VMA were not associated with VA. Eyes with VMT or VMA treated as needed required on average 2 more injections over 2 years.